The Role of Accounting Training in Top Management Decision Making. - Dalton, Francis E.; Miner, John B. (The Accounting Review, 1970)
Accounting professors, and a number of other business administration professors as well, have argued that a solid background in accounting is necessary for effective corporate decision making. By implication and on occasion explicitly, they indicate that top management would be more successful and produce higher profits, if men with considerable accounting training were more numerous at the very highest levels. This article reports on several studies that investigate this hypothesis. The medium of investigation is a simulation of top management decision-making in manufacturing industry. That accounting training is not an essential factor in management success, at least within the manufacturing sector, seems inescapable. Prior research has indicated that intelligence may be a factor in game performance; steps were taken to ensure that differences on this factor could not influence the results. Thus, as with homogeneity of major, the objective was to eliminate a possible contaminating variable which might become confounded with the experimental variable accounting training and make unambiguous interpretation of results impossible.